Howard Rachlin: An extended scientist. Issue 1 (14th December 2022) - Locey, Matthew L.
Abstract : During the latter half of his career, Rachlin's work increasingly focused on integrating the study of temporal discounting and social cooperation—choices for an extended self. His notion of a self that is extended across time and social space is a useful framework within which to consider Rachlin's impact as a philosopher, scientist, and mentor over the course of his 56‐year career in behavior science.